Parâmetros de qualidade em leite cru refrigerado em propriedades de base familiar na região sul do Espírito Santo - Nascimento Neta, Francisca Carvalho do (2013)
Milk production has socioeconomic importance for family farmers in the State of Espírito Santo and the municipality of Alegre-ES. The aim of this study was to evaluate the conditions of production and hygienic-sanitary quality of raw milk obtained from cooling tanks located in rural communities in the municipality of Alegre-ES and to investigate the presence of antibiotic residues in milk. It was applied to a previously structured questionnaire based on the requirements of the legislation of the Ministério da Agricultura Pecuária e Abastecimento (BRAZIL, 2008) on 34 farms from February 2012 to June 2012. It was obtained data about the cleanliness and physical structure of barns, the origin and existence of water treatment, type of milking, conduct and hygiene of food handlers, health control of manipulators, cleaning and sanitizing procedures at cleaning of teats, type of material used for drying off teats and the realization of sanitary control in relation to mastitis, and the treatment and transport of milk. In response to the questionnaire, it was observed that low level of education prevails among producers. The location of the barn was good: they were airy, dry and clean; all barns are covered and minority owned cemented floor and milking parlor. Almost all of the properties produce less than 100 liters per day and practice manual milking. Every owners control for endoparasites and ectoparasites, and have vaccinate of cattle against foot and mouth disease (FMD), 94.1% against rabies and 91.2% against brucellosis. At half of the properties, teats are cleaned before milking; few performed the pre-dipping and post-dipping. At all properties have treatment for mastitis, but only, one fifth used strip cup for mastitis test. And there was no treatment of the water used in the barns. All milk produced is transported by milk tanker trailers and most of it has the cooperatives as a destination. All equipment used for milking is sanitized, but the minority used sanitizer. Few handlers had adopted the habit of bathing before performing milking. Few of them have had training or lectures about standards established by IN 62. In the evaluation of refrigerated raw milk with the workers, and reception facilities, it was observed that none had protection against entries of insects and rodents, and environmental contaminants; none had milk cans and utensil washer; facilities were poorly designed and not allow the appropriate application of sanitary practices; hygienic conditions are extremely poor and undermine the maintenance of milk quality; none has a proper procedure for cleaning equipment. Workers of collector points do not take baths before starting the activities or wear specific clothes; they do not perform regular health check up, and do not adopt any system for water treatment used in storage tanks. Also, It was evaluated the sanitary, physical chemical qualities of raw milk samples from four storage tanks called T1, T2, T3 and T4. The results in physical and chemical analyzes were presented mostly in accordance with the standards set by IN 62, except that the pH value showed a change, which may be indicative of the addition of alkali or possible presence of mastitis in the herd. The mean values detected in the microbiological analysis were: Total Bacterial Count CBT 1.4 x106 CFU.mL-1, psychotropic 6.1x105 CFU.mL-1 , total Coliforms 8.5x104 CFU.mL-1 , Staphylococcus spp. CFU.mL-1 2.9 x105 and Escherichia coli CFU.mL-1 4.4 x104 . The results about analyzes of milk showed up outside the microbiological standards required by law. The values detected for some tanks in analyzes, CBT 6.0x105 CFU.mL-1 , is outside the standards of IN 62 in 50% of samples. There was no antibiotic residue in milk analyzed. There is a need for adjustments and improvements in production traits and milk cooling tanks, as well the implementation of the Good Practice Livestock Production on farms to ensure food safety and sustainability of dairy farming at region.